Unorthodox Nanocatalysis through a Carbosphere-Nanofabricated Pt–Si Nanocomposite: Effective Tandem Imination Protocol Involving Oxidative C=C Cleavage - Mandal, Prakash K.; Atta, Sanghamitra; Debnath, Sudipto; Samai, Subhasis; Laha, Radha Madhab; Manna, Anindya S.; Mitra, Soumyadeep; Saha, Koushik; Maiti, Dilip K. (Synlett, 2025)
Considering the efficacy of platinum nanoparticles in various research areas, we report a new carbosphere-nanofabricated Pt–Si nanocomposite with a size of ca. 8 nm as measured using HRTEM and DLS. This nanocomposite was synthesized by an eco-friendly hydrothermal approach using an efficient and unprecedented in situ imination through oxidative C=C cleavage. Based on HRMS kinetic studies and control experiments, a plausible mechanistic approach was developed in which the olefin counterpart is converted into the corresponding aldehyde by exploiting Pt–Si mediated nanocatalysis. The major advantages of this work include the eco-friendly hydrothermal synthesis of the Pt–Si nanocomposite for the non-traditional imination from cinnamic acid or styrene derivatives with diverse amines through oxidative cleavage of the C=C bond. The method will find diverse applications in late-stage functionalizations.
Keywords: Pt-Si nanocomposites; hydrothermal methods; oxidative cleavage of C=C bonds; direct imination; nanocatalysis